Effectiveness of Personalized Multifactorial Fall Risk Assessment and Intervention in Reducing Fall Rates Among Older Adults: A Retrospective Study - Piyapat Dajpratham; Poungkaew Thitisakulchai; Rinlada Pongratanakul; Rachaporn Prapavanond; Sirapat Haridravedh; Weerasak Muangpaisan (Siriraj Medical Journal)
Objective: This study aimed to investigate the effectiveness of personalized multifactorial fall risk assessment and intervention in reducing the incidence of recurrent falls after one year.